WEBINARS & WORKSHOPS INTRODUCTION TO COMPUTER VISION: UNRAVELING THE WONDERS OF COMPUTER VISION - Dwi Duta Mahardewantoro; Amili, Fadel; Ilyasa, Fahri; Ikhsan Adi Prayogo; Ikhsan Fitriansyah; Muhammad Arif; Rifqi Baihaqi Sabhan; Syuja Ardyansyach; Muhammad Adri Farqan; Nurvelly Rosanti; Poppy Meilina; Nurbaya Ambo, Sitti (CV. Alina, 2024)
The computer vision workshop is a crucial platform addressing the escalating demands of this rapidly evolving field within computer science. In today's era, visual data processing is integral across diverse sectors such as healthcare, security, and industry, making the workshop a guiding beacon for participants navigating the complex terrain of computer vision. Central to its agenda is the dissemination of practical insights into training data for object recognition, a cornerstone for unleashing the full potential of computer vision applications. Participants delve into fundamental concepts, encompassing nuances of deep learning alongside the intricacies of data training and object detection. Employing Google Colab and Python programming language, the workshop emphasizes practical application, equipping participants with cutting-edge tools. Expected outcomes encompass participants fostering a profound grasp of underlying principles, refining proficiency in data training for nuanced object detection, and bolstering confidence through hands-on exercises. Designed holistically, the workshop integrates elements such as deep learning, computer vision, interactive Q&A sessions, and practical exercises, ensuring participants acquire a robust skill set ready for real-world challenges in the dynamic realm of computer vision.